Psilocybin: crystal structure solutions enable phase analysis of prior art and recently patented examples. Issue 1 (20th December 2021) - Sherwood, Alexander M.; Kargbo, Robert B.; Kaylo, Kristi W.; Cozzi, Nicholas V.; Meisenheimer, Poncho; Kaduk, James A.
Abstract : The crystal structures of anhydrous psilocybin Forms A and B have been solved using laboratory powder X‐ray diffraction data, refined using synchrotron and laboratory data, and optimized by applying density functional techniques. The crystal structures, along with that of the previously determined trihydrate, permit the quantitative analysis of a variety of historical samples of psilocybin. Abstract : Psilocybin systematic name: 3‐[2‐(dimethylamino)ethyl]‐1 H ‐indol‐4‐yl dihydrogen phosphate is a zwitterionic tryptamine natural product found in numerous species of fungi known for their psychoactive properties. Following its structural elucidation and chemical synthesis in 1959, purified synthetic psilocybin has been evaluated in clinical trials and has shown promise in the treatment of various mental health disorders. In a recent process‐scale crystallization investigation, three crystalline forms of psilocybin were repeatedly observed: Hydrate A, Polymorph A, and Polymorph B. The crystal structure for Hydrate A was solved previously by single‐crystal X‐ray diffraction. This article presents new crystal structure solutions for the two anhydrates, Polymorphs A and B, based on Rietveld refinement using laboratory and synchrotron X‐ray diffraction data, and density functional theory (DFT) calculations. Utilizing the three solved structures, an investigation was conducted via Rietveld method (RM) based quantitative phase analysis (QPA) to estimate the contribution of the three different forms in powder X‐ray diffraction (PXRD) patterns provided by different sources of bulk psilocybin produced between 1963 and 2021. Over the last 57 years, each of these samples quantitatively reflect one or more of the hydrate and anhydrate polymorphs. In addition to quantitatively evaluating the composition of each sample, this article evaluates correlations between the crystal forms present, corresponding process methods, sample age, and storage conditions. Furthermore, revision is recommended on characterizations in recently granted patents that include descriptions of crystalline psilocybin inappropriately reported as a single‐phase `isostructural variant.' Rietveld refinement demonstrated that the claimed material was composed of approximately 81% Polymorph A and 19% Polymorph B, both of which have been identified in historical samples. In this article, we show conclusively that all published data can be explained in terms of three well‐defined forms of psilocybin and that no additional forms are needed to explain the diffraction patterns.